2014
DOI: 10.3109/15412555.2014.898039
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of COPD by Disease Severity in Men and Women in Northern Vietnam

Abstract: The prevalence of COPD and its risk factor pattern varies between different areas of the world. The aim of this study was to investigate the prevalence of COPD by disease severity in men and women and risk factors for COPD in northern Vietnam. From all 5782 responders to a questionnaire survey, a randomly selected sample of 1500 subjects was invited to a clinical follow-up study. The methods included a structured interview using a modified GA2LEN study questionnaire for registration of symptoms and possible de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
0
16
0
1
Order By: Relevance
“…This trend has been observed in many studies [ 15 17 ] and can be explained by greater exposure to risk factors and physiological decrease in lung function with age. In epidemiological studies, high prevalence of COPD in the elderly has been reported widely, in age groups > 50 years [ 18 ], 55–70 years [ 19 ], ≥ 60 years [ 20 ], 75–84 years [ 21 ], ≥ 70 years [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This trend has been observed in many studies [ 15 17 ] and can be explained by greater exposure to risk factors and physiological decrease in lung function with age. In epidemiological studies, high prevalence of COPD in the elderly has been reported widely, in age groups > 50 years [ 18 ], 55–70 years [ 19 ], ≥ 60 years [ 20 ], 75–84 years [ 21 ], ≥ 70 years [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The COPD prevalence estimates based on spirometry reported in this study were similar to the data published in previous studies (45 in Spain [ 16 ], 42 in USA [ 19 ] and 37 in United Arab Emirates [ 22 ] per 1000). Some other studies reported higher estimates (240 (The Netherlands) [ 23 ], 218 (Russia) [ 26 ], 197 (Uruguay) [ 20 ], 184 (Greece) [ 15 ], 162 (Uganda) [ 27 ], 162 (Sweden) [ 21 ], 142 (Portugal) [ 28 ], 134 (Korea) [ 17 ], 78 (Mexico) [ 20 ] and 71 (Vietnam) [ 18 ] per 1000). The variability in prevalence estimates could reflect true differences or be due to the different methodologies used in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…A study using a prevalence model to estimate burden of COPD in 12 Asian countries, reported a COPD prevalence rate of 6.7% in Vietnam [12]. A more recent one conducted on patients in the north of Vietnam indicated the result of 7.1% prevalence [13]. Exacerbations were found to occur in over half of COPD patients [14], resulting in them having to attend hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…With an estimated 328 million people presenting moderate to severe COPD worldwide, the condition is considered as a major health and economic concern globally, and more specifically in low- and middle-income countries (LMICs) where almost 90% of worldwide COPD deaths are reported [ 2 , 3 ]. Approximately 7.1% of the Vietnamese population (nearly 6.8 million people) have COPD [ 4 ]. These patients occupy roughly 25% of the beds in the respiratory wards of hospitals, at our institution [ 5 ], and nationwide [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 7.1% of the Vietnamese population (nearly 6.8 million people) have COPD [ 4 ]. These patients occupy roughly 25% of the beds in the respiratory wards of hospitals, at our institution [ 5 ], and nationwide [ 4 ].…”
Section: Introductionmentioning
confidence: 99%